Voluntary contributions 'vote out' public ones - Aleix Calveras; Juan-José Ganuza; Gerard Llobet (SERIEs - Journal of the Spanish Economic Association, 2011)
In a relatively recent paper, Gehrig and Stenbacka (Eur Econ Rev 51, 77-99, 2007) show that information sharing increases banks' profits to the detriment of creditworthy entrepreneurs in a model of a banking duopoly with switching costs and poaching. They restrict their analysis to the case in which adverse selection is not too strong.We analyze the complementary case and show that, when the economy suffers from strong adverse selection, information sharing still increases banks' profits, but it may or may not hurt talented entrepreneurs.
Keywords: G21; L15; D82; 330; information sharing; lending relationships; poaching; equilibrium switching; Öffentliche Güter; Allokation; Externer Effekt; Neue politische Ökonomie; Theorie